Impacts of Fire on Forest Biomass Dynamics at the Southern Amazon Edge. (19th July 2019) - Nogueira, Denis S; Marimon, Beatriz S; Marimon-Junior, Ben Hur; Oliveira, Edmar A; Morandi, Paulo; Reis, Simone M; Elias, Fernando; Neves, Eder C; Feldpausch, Ted R; Lloyd, Jon; Phillips, Oliver L
Summary: Over recent decades, biomass gains in remaining old-growth Amazonia forests have declined due to environmental change. Amazonia's huge size and complexity makes understanding these changes, drivers, and consequences very challenging. Here, using a network of permanent monitoring plots at the Amazon–Cerrado transition, we quantify recent biomass carbon changes and explore their environmental drivers. Our study area covers 30 plots of upland and riparian forests sampled at least twice between 1996 and 2016 and subject to various levels of fire and drought. Using these plots, we aimed to: (1) estimate the long-term biomass change rate; (2) determine the extent to which forest changes are influenced by forest type; and (3) assess the threat to forests from ongoing environmental change. Overall, there was no net change in biomass, but there was clear variation among different forest types. Burning occurred at least once in 8 of the 12 riparian forests, while only 1 of the 18 upland forests burned, resulting in losses of carbon in burned riparian forests. Net biomass gains prevailed among other riparian and upland forests throughout Amazonia. Our results reveal an unanticipated vulnerability of riparian forests to fire, likely aggravated by drought, and threatening ecosystem conservation at the Amazon southern margins.